2007
DOI: 10.1523/jneurosci.4926-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Rho Regulates Membrane Transport in the Endocytic Pathway to Control Plasma Membrane Specialization in Oligodendroglial Cells

Abstract: Differentiation of oligodendrocytes is associated with dramatic changes in plasma membrane structure, culminating in the formation of myelin membrane sheaths. Previous results have provided evidence that regulation of endocytosis may represent a mechanism to control myelin membrane growth. Immature oligodendrocytes have a high rate of clathrin-independent endocytosis for the transport of membrane to late endosomes/lysosomes (LE/Ls). After maturation and receiving signals from neurons, endocytosis is reduced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 63 publications
(69 reference statements)
2
50
0
Order By: Relevance
“…LE/Lys localization of PLP and VAMP7 is consistent with the literature (Advani et al, 1999;Krämer et al, 2001;Feldmann et al, 2009). It has been shown that PLP accumulates in LE/Lys on clathrin-independent cholesterol-dependent endocytosis, and furthermore, retranslocation of PLP from LE/Lys storage sites to the plasma membrane is regulated by RhoGTPase inactivation triggered by a soluble neuronal signal Kippert et al, 2007). Recycling through LE/Lys facilitates association of PLP with membranes exhibiting specific myelin characteristics (Winterstein et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…LE/Lys localization of PLP and VAMP7 is consistent with the literature (Advani et al, 1999;Krämer et al, 2001;Feldmann et al, 2009). It has been shown that PLP accumulates in LE/Lys on clathrin-independent cholesterol-dependent endocytosis, and furthermore, retranslocation of PLP from LE/Lys storage sites to the plasma membrane is regulated by RhoGTPase inactivation triggered by a soluble neuronal signal Kippert et al, 2007). Recycling through LE/Lys facilitates association of PLP with membranes exhibiting specific myelin characteristics (Winterstein et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…There is accumulating evidence that oligodendrocytes, which simultaneously assemble myelin sheaths at multiple subcellular sites, use endosomes as local internal membrane sorting and storage compartments, from which membrane is rapidly recruited to the sites of membrane growth controlled by neuronal signaling Kippert et al, 2007;Winterstein et al, 2008). Our study demonstrates that VAMP3 and VAMP7 mediate surface delivery from RE and LE/Lys, respectively.…”
Section: Role Of Vamp3 and Vamp7 In Myelinationmentioning
confidence: 69%
“…Of interest, a similar correlation between downregulation of acto-myosin contractility and membrane extension has been recently described during morphological differentiation of oligodendrocytes (Kippert et al, 2009), suggesting that despite their different morphologies and modes of myelination, the mechanisms controlling plasma membrane expansion by myelinating glial cells require local release of myosin-II-mediated contraction and relaxation of the actin cytoskeleton. Whether MLCK activity also plays a role in oligodendrocyte remodeling and differentiation awaits further study, but inactivation of RhoA and ROCK as well as inhibition of myosin II have been shown to promote membrane expansion and oligodendrocyte branching and differentiation (Kippert et al, 2007;Wang et al, 2008;Wolf et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated recently that soluble factors secreted from neurons induce a reduction in clathrinindependent endocytosis and a stimulation of exocytosis of PLP in cultured oligodendrocytes, which is regulated by Rho-GTPase activity levels (Kippert et al, 2007;Trajkovic et al, 2006). Thus, neuron-to-glia signaling regulates endocytic trafficking of the major myelin protein allowing target-oriented tuning of myelin membrane traffic.…”
Section: Journal Of Cell Science 121 (6) Endocytic Trafficking Of Myementioning
confidence: 99%